If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(w+8)=6w-20
We move all terms to the left:
2(w+8)-(6w-20)=0
We multiply parentheses
2w-(6w-20)+16=0
We get rid of parentheses
2w-6w+20+16=0
We add all the numbers together, and all the variables
-4w+36=0
We move all terms containing w to the left, all other terms to the right
-4w=-36
w=-36/-4
w=+9
| 180=a+a+64 | | -7x+9=39 | | 5q+3q+–3q=–15 | | 16x^2+9x+65=0 | | 4^7+x=31 | | 12.40=6x | | 2y+8y–2=4y–6+4 | | -6(w+1)=2w-4+5(2w+2) | | 72/y=12 | | 4x7+x=31 | | y=575(1-0.06)^3 | | 4x+-5(2x+1)=-6+5 | | a-64=36 | | 5(x−3)−7=−2(x+4)+1 | | 9(2y-9)-(9y+5)=0 | | 15+5xx=12 | | 4x+-5(2x+1)=1+-5 | | 5/6=x+1/2 | | 6w=990 | | 11x-6+4x+13+79=90 | | 4j=672 | | 16.4=8x | | 2f=414 | | 18x-9x=72 | | 4x+-5(2x+1)=0+-5 | | 6.75=3x | | 31z=744 | | 12.5=x+4.68 | | 8s+70=180 | | j+17/6=5 | | 60/5yy=7-5 | | 10.1=t7.2 |